Practical Handbook for Small-Gauge Vitrectomy A Step-By-Step Introduction to Surgical Techniques - Spandau, Ulrich (Springer International Publishing, 2018)
Since publication of the first edition of this book in 2012 vitreoretinal surgery has marched with huge steps forward. In 2012 23G was standard, today 25G and 27G are the most commonly used gauge sizes for vitrectomy. In 2012 the cutting rate was 5.000 cuts/min and today with the development of a novel vitreous cutter the cutting rate has increased to 16.000 cuts/min. The advent of 25G/27G made the instruments smaller and surgery less traumatic. Practical Handbook for Small-Gauge Vitrectomy: A Step-By-Step Introduction to Surgical Techniques, 2ndEdition focuses on these new developments and features new chapters on PVR detachment, intraocular tumour, macular translocation, sub macular hemorrhages and ocular trauma. The surgeries are demonstrated step-by-step and the material is shown in detail and videos visualize the surgery.This book will serve as an immensely useful guide for all surgeons who are intending to make use of this exciting and increasingly used technique.